(untitled) (Salam International Academic Journal, 2014)
This article is written on the “Computer and Internet Crimes”. The study with its descriptive and analytical method, sought to identify the modern crimes through computer and internet that have occurred in majority of the countries of the world and is growing every day. Although, computer and internet are the tools that has drastically changed our world and has provided mankind with facilities and information. However, with the development of computer technology and internet, the crime has also emerged at the international level being called as Computer or Internet Crimes. Computer crimes are those illegal acts committed by a person using computer. Internet crimes are those illegal acts committed by a person using internet. In most of the countries of the world today, these crimes are considered very critical and countries seek to enact rules and laws and try findings ways to prevent this crime. Unfortunately, in our beloved Afghanistan, there is still no attention being paid towards coping with this critical issue.